Innovational perspectives - contributions to the national conception for regional development in Hungary - FARKAS, János; KRÉMER, András; MÁTYÁSI, Sándor; TAMÁS, Pál; VÁRNAI, Gábor (European Spatial Research and Policy, 1996)
The primary aim of !his study has been to provide a contribution to the National Conception for Regional Development towards working out a regional policy in Hungary which takes into account the innovational potentials of individual regions, strengthens potentials or, as far as possible, creates them wherever they are lacking.